MODERATOR KONTEN DALAM KAITANNYA MENINGKATKAN CITRA MARKETPLACE - Ningsih, Masnia; Dewi, Ratnaningrum Zusyana (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2022)
A positive image is absolutely essential for a business company in the era of communication, so various innovations and creativity are needed by companies in an effort to gain sympathy and trust or trust from the public. One of the forms of business carried out by the Marketplace is by cooperating with a content moderation company, where the function of limiting or filtering content is to assist Marketplace companies in dealing with an increasingly critical society or public where they expect the fulfillment of accurate and of course positive information services. who can convince themselves (the public) and not cause doubts when transacting on the Marketplace. Using a descriptive analysis method, this study examines content moderators in terms of enhancing the image of the Marketplace. The achievement of a positive Marketplace company image when connected with the activities of content moderators will appear in the increase in the number of users of certain Marketplace services as evidence that the public places more trust and gains comfort and security when making transactions in it. The end result of achieving a positive image is the existence and sustainability of Marketplace companies in the long term.